Potensi dan Peluang Birdwatching di Taman Hutan Raya (Tahura) Banten - Umam, Chotibul; Ingkadijaya, Rahmat; Osman, Ismeth Emier (Jurnal Ilmiah Pariwisata, 2023)
Taman Hutan Raya (tahura) banten has a natural tourist attractions, such as waterfalls is curug gendang and curug puteri which are often visited by tourists. on the other hand, tahura banten also has a diversity of fauna in the form of endemic birds which are suspected to be a special interest tourist attraction. the purpose of the study was to identify the potential and opportunities of tahura banten as a birdwatching. observations, interviews and documentation were carried out at tahura banten to obtain data on the potential and opportunities for birdwatching with focus group discussions (fgd) with local governments and tourism actors. swot analysis is carried out to formulate a strategy for the tourism component. based on the analysis, the potential for birdwatching tourism in tahura banten found six endemic bird species, tahura banten is also one of the target bird watchers of endemic species on the island of java. in order for the potential strategy and opportunities for bird watching in tahura banten to be implemented, it is necessary to improve the quality of services and improve the quality of tourist facilities. Keywords: Tahura Banten, Birdwatching, Endemic Birds